Answer: 9x + 2(2x + 3) = 13x + 6
Explanation:
To have an equation with infinitely many solutions, we need everything to "cancel out" after simplifying the equation down using reverse operations.
This means we need to have the coeffiecnets of x and constants on each side be the same. This way, when we subtract one to simplify then "cancel out" leaving us with nothing.
Given:
9x + 2(2x + 3) = ___ x + ___
Simplify the left side:
9x + 4x + 6 = ___ x + ___
Combine like terms:
13x + 6 = ___ x + ___
Find values that work:
13x + 6 = 13x + 6
If you attempt to solve, you end up with 0 = 0, giving us infinite solutions.